The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Publisher: Institute for Security Studies (ISS)
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Coesão social e violência política em Moçambique: notas para debate - Forquilha, Salvador; Gonçalves, Euclides (2019)
Perguntas e método de pesquisa Contexto: • Dados da primeira fase de uma pesquisa programática no norte de Moçambique Pergunta: • Como operacionalizar operacionalizar a noção de coesão social em Moçambique? • Que subsídios a noção de coesão social pode oferecer para a compreensão da violência política em Moçambique? Recolha de dados • Período: Abril e Maio de 2019 • Locais: Cidade de Maputo, Chiúre (Cabo Delgado), Chimbunila (Niassa) e Mussuril (Nampula) • Entrevistas: Representantes e membros de partidos políticos, líderes comunitários e religiosos, grupos de camponeses e jovens • Análise de dados: Mapeamento de factores com potencial para conflicto (conflict mapping)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Conferência Internacional Sobre a Educação da Rapariga - ROSC (ROSC - Fórum da Sociedade Civil para os Direitos da Criança, 2019)
O Movimento de Educação para Todos (MEPT) em coordenação com o Ministério da Educação e Desenvolvimento Humano (MINEDH), realizou nos dias 6 e 7 de Junho do corrente ano, em Maputo, a Conferência Internacional Sobre a Educação da Rapariga com o lema “Desafios, Partilha de Experiências e Boas Práticas para Assegurar a Retenção da Rapariga no Sistema de Ensino.” Esta conferência tinha como objetivos: → Troca de experiências em torno de políticas e práticas existentes a nível nacional e internacional para assegurar a retenção da rapariga no sistema de ensino e discutir estratégias e possíveis soluções para a redução dos índices de abandono escolar por parte das raparigas na África Subsariana; → Apreciar os instrumentos e experiências existentes para prevenir a gravidez infantil e combater a violência baseada no género nas escolas a nível da região; → Olhar para os instrumentos e experiências existentes de boas práticas na região para o tratamento de casos de alunas grávidas nas escolas e a sua reintegração.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género

Tanzaniano recruta jovens no Niassa para ataques em Cabo Delgado - Governo de Moçambique (Governo de Moçambique, 2019)
Alguns jovens do distrito de Mecula, no Niassa, norte de Moçambique, são recrutados para integrarem o grupo de malfeitores que protagonizam ataques armados nos distritos do norte da vizinha província de Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Niassa; L - portuguese / português; youth / juventude

Input subsidies in Mozambique: The future of peasant farmers and their seed systems - Lewis, Linzi (African Centre for Biodiversity, 2019)
In this paper, we discuss and assess the input subsidy programmes in Mozambique, as part of the larger agriculture policy landscape, the impact this has had on the agricultural sector in Mozambique, and particularly on smallholder farmers. Input subsidy programmes in Mozambique are fragmented and operate more along the lines of projects and pilots. Therefore, this paper selects a few key projects to explore approaches being taken by the Mozambican government, along with international donors, providing agricultural inputs to peasant farmers. Notably we consider the more recent Food and Agriculture Organization (FAO)’s input subsidy programme, and the World Bank funded Agriculture and Natural Resources Landscape Management (SUSTENTA) programme/project, implemented by the National Sustainable Development Fund2 (FNDS), under the Ministry of Land, Environment and Rural Development (MITADER). This paper provides a brief background to agriculture in Mozambique, followed by the agricultural policies, plans and budgets guiding agricultural investments in the country. After briefly outlining the agricultural sector – notably seed, fertiliser and agro-dealers in the country – we discuss and analyse selected input subsidy programmes in Mozambique. The paper closes with a conclusion and recommendations to feed into future discussions with farmers, farmer organisations, non-governmental organisations (NGOs) and others in Mozambique.
978-0-6399760-4-4
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Subsídios em insumos em Moçambique: O futuro dos agricultores camponeses e dos seus sistemas de sementes - Lewis, Linzi (African Centre for Biodiversity, 2019)
Neste artigo, discutimos e avaliamos os programas de subsídios em insumos em Moçambique, como parte do panorama mais amplo da política agrícola, o impacto que estes têm tido no sector agrícola em Moçambique e particularmente nos pequenos agricultores. Os programas de subsídios em Moçambique são fragmentados e operam mais ao logo das linhas de projectos e pilotos. Este artigo selecciona, portanto, alguns dos projectos principais para explorar abordagens que estão a ser usadas pelo governo Moçambicano, juntamente com doadores internacionais, para fornecer insumos agrícolas aos produtores camponeses. Notavelmente consideramos o programa de subsídios em insumos mais recente da FAO (Organização para Alimentação e Agricultura), e o projecto/ Programa Agrícola e de Gestão de Paisagens de Recursos Naturais (SUSTENTA) financiado pelo Banco Mundial, implementado pelo Fundo Nacional de Desenvolvimento Sustentável (FNDS), debaixo do Ministério da Terra, Ambiente e Desenvolvimento Rural (MITADER). Este ensaio oferece um breve histórico da agricultura em Moçambique, seguido por políticas, planos e orçamentos agrícolas que guiam os investimentos agrícolas no país. Após brevemente esboçar o sector agrícola – nomeadamente os vendedores de sementes, de fertilizantes e de agroinsumos no país – – discutimos e analisamos programas seleccionados de subsídios em insumos em Moçambique. O artigo encerra com uma conclusão e com recomendações para contribuir para discussões futuras com agricultores, organizações de agricultores, organizações não-governamentais (ONGs) e outros em Moçambique.
ISBN: 978-0-6399760-5-1
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Resultados Definitivos: Censo 2017 - Instituto Nacional de Estatística - INE (2019)
O Censo foi realizado em todo o País de 1 a 15 de Agosto de 2017.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Publisher: Routledge
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

One-stop service policy as a bureaucratic reform in Indonesia - Umar, Akmal; Madani, Muhlis; Amrin; Farida, Umi; Yusriadi, Yusriadi; Elpisah; Bin Tahir, Saidna; Sakkir, Geminastiti (Academy of Strategic Management Journal, 2019)
Bureaucratic reform is an effort to improve the system of government administration, especially institutional aspects, management, and human resources of the apparatus. One of the bureaucratic reforms in Indonesia is the establishment of the One-Stop Service (OSS) office which handles and integrates all forms of licensing. This article examined how the implementation of public service reform and how the change of management practices had been implemented in the OSS of Bone Regency. Data were collected through a semi-structured interview with 16 of OSS' employees and nine service-users. This study applied a qualitative approach using a case study design. Techniques of data collection used three kinds of
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Cyclones Idai and Kenneth - OCHA (United Nations Office for the Coordination of Humanitarian Affairs, 2019)
In March and April 2019, Southern Africa was hit by two subsequent cyclones that left a trail of destruction in their path, and close to 2.2 million people in need urgent assistance in Mozambique alone. On the night of 14 to 15 March Tropical Cyclone Idai made landfall near Beira City, Sofala Province, in central Mozambique. The cyclone brought torrential rains and winds to Sofala, Zambezia, Manica and Inhambane provinces. Cyclone Idai continued across land as a Tropical Storm and hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. Idai left more than 600 people dead and an estimated 1.85 million people in need in Mozambique alone. On 24 April, Tropical Cyclone Kenneth passed north of the Comoros Islands, hitting the northern island of Ngazidja. On the evening of 25 April, the cyclone made landfall in Mozambique between the districts of Macomia and Mocimboa da Praia in Cabo Delgado province. With wind gusts of up to 220km/h, Tropical Cyclone Kenneth became the strongest cyclone to ever hit the African continent. Cyclone Kenneth left 374,000 people in need. Tropical Cyclone Kenneth reportedly caused three deaths, at least 20 injuries and extensive damage to houses across the archipelago. Preliminary estimates indicate that at least 1,000 people were displaced, most of them children. While assessments are ongoing, initial reports from the Comoros indicate that several villages were flooded due to sea surges and broken dykes, and that power was cut in multiple locations. Roads have reportedly been damaged and cut off by fallen trees, while telephone poles are down in multiple locations. Latest updates on the response can be found here. It is the first time in recorded history that two strong tropical cyclones have hit Mozambique in the same season. Cyclone Idai As of 9 April, the official death toll caused by Cyclone Idai stands at 602 people, with more than 1,600 people injured, according to the Government. Many people are displaced, and communicable diseases are on the rise. Of particular concern are cholera and malaria. An oral vaccination campaign reached over 800,000 people by early April 2018. Many schools are damaged or used as shelter for displaced people. Humanitarian partners continue to call for any relocations out of schools or elsewhere to be safe, dignified and voluntary. In figures People in need 1.85M People targeted 1.72M Funding needed $282M Cyclone Kenneth The cyclone hit Mozambique more north than Cyclone Idai, with Quissanga, Macomia, and Ibo districts in Cabo Delgado hardest-hit, according to preliminary government reports. At least 45 deaths have been reported and 18,029 people were initially reportedly displaced, according to the National Disaster Management Institute (INGC). Cyclone Kenneth made landfall at the end of the rainy season, when river levels were already high, increasing the risk of river flooding. Humanitarian needs in Mozambique have sky-rocketed, and the humanitarian response will need to rapidly scale-up while capacity and funding are limited. In figures People in need 374K People targeted 374K Funding needed $104M On 16 March, Cyclone Idai hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. The homes of at least 4,000 households are destroyed or currently uninhabitable. The seven districts affected by Cyclone Idai- Chipinge, Chimanimani, Buhera, Bikita, Mutare, Gutu, and Chiredzi - multisectoral support will be required to speed recovery. The livelihoods of over 270,000 people across these districts has been affected. Those lviing in Chipinge and Chimanimani districts are worst hit. In early March, heavy rains and flooding linked to Cyclone Idai killed 60 people, displaced nearly 87,000 people and affected nearly 870,000 persons. The Government of Malawi declared a ‘state of disaster’ on 8 March and subsequently launched a Flood Response Plan and Appeal on 28 March to support life-saving humanitarian interventions in 15 affected districts. Humanitarian partners and the Government of Malawi have reached over 400,000 persons with immediate life-saving relief support which includes food, medicine, shelter, protection services and other non-food-items such as water, sanitation and hygiene supplies. A Post Disaster Needs Assessment (PDNA) has been undertaken by the Malawi Government, UN, World Bank and European Union to assess damages, losses and priority recovery needs and costs. The data and information collected will inform the Government’s recovery plan.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; natural disasters / desastres naturais

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

Recent evidence of the development of micro, small and medium enterprises in Indonesia - Tambunan, Tulus (Journal of Global Entrepreneurship Research, 2019)
This paper examines the development of micro, small and medium enterprises (MSMEs) in Indonesia. It has three research issues, namely the role of MSMEs, their constraints, and the importance of MSMEs for the creation of business opportunities for women. More specifically, the study aims to answer the following research questions. First, how important are MSMEs in Indonesia? Second, what are their main constraints? Third, how important are they, especially micro and small enterprises (MSEs), for the creation of business opportunities for women? Fourth, is the growth of MSEs a sign of increased entrepreneurial spirit or a reflection of poverty? This study adopted descriptive analysis using secondary data. It shows that MSMEs in Indonesia are dominated by MSEs, and accounted for almost 100% of all existing firms but only contributed between 58 to 61% of gross domestic product (GDP). About 42.84% of MSEs are owned by women, although the ratio of female to male entrepreneurs in MSEs varies by province. Poverty seems to be the main force behind the growth of MSEs. This study ends with some policy recommendations that the government should: (i) conduct trainings that focus on online marketing, entrepreneurship, management, and improving the quality of product and business efficiency; (ii) provide alternative funding facilities with low interest rates and non-burdensome requirements; and (iii) provide assistance directly in the production site for new entrepreneurs in their first years of running businesses. In addition, all gender discrimination treatments that have been burdensome for women to run own businesses must be eliminated. This study has, however, several limitations, especially with respect to the third and fourth research questions. Secondary data used does not have information about the main/initial motivation of MSME owners to run their own business and their socio-economic profiles.
Number: 1
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Transition from Civil War to Peace: The Role of the United Nations and International Community in Mozambique - Adedokun, Ayokunu (Peace and Conflict Studies, 2019)
With the heavy involvement of the United Nations (UN) and the international community, the Rome General Peace Agreement of 1992 ended more than 16 years of civil war in Mozambique. The peace agreement and post-conflict initiatives by the international community was successful in transforming the Mozambique National Resistance (Renamo) from a rebel group into a viable political party. Key components of the United Nations and the broader international community success in negotiating peace and creating conditions for political stability and democracy in Mozambique were (a) the provision of disarmament, demobilization and reintegration (DDR) before democratisation, (b) decentralization of humanitarian and relief efforts to provincial and district levels, (c) provision of financial support directly for the development of political parties, and (d) budget support to sectors relevant to peacebuilding. Though imperfect, Mozambique remains an important case study in how the UN and international community can help in post-conflict environments. Thus, the paper argues that success in peacebuilding operations depends on credible and impartial international support through the UN, as opposed to peacebuilding operations through the United States of America or Russia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Anuário Estatístico - Statistical Yearbook 2018 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2019)
À semelhança das edições anteriores, o Anuário Estatístico 2018 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Representação Comunitária na Gestão de Terras e Recursos Naturais. Nota Técnica - Salomão, Alda; Mário, T. V.; Tanner, Christopher (SPEED+; USAID, 2019)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento